(untitled) (Asian Journal of Medical and Biological Research, 2017)
An experiment was carried out from November, 2014 to February, 2015 at Dinajpur, Bangladesh to quantify the total water requirement of Strawberry for three indigenous cultivars RU-1, RU-2 and RU-3by using 12’’ × 11.5’’ Bucket-Type Lysimeter. Water requirement in zero evaporation condition for RU-1, RU-2 and RU-3 were 86.25 ± 0.23, 49.22 ± 0.31 and 73.42 ± 0.42mm respectively, which were significantly different (p< 0.01). After adding field evaporation total water requirement RU-1, RU-2 and RU-3 were 351.45 ± 0.23, 324.42 ± 0.31 and 338.61 ± 0.42mm respectively.ET0(Potential evapotranspiration)value ranged between3.21-4.56 (mm/day) while seasonal ET0 was approximately 457 (mm/season).ETc (Evapotranspiration) value measured by using Kc (Crop coefficient) value and equations provided by FAO, (2016a, b) viz. 324.24 (mm/season). As plant only uses less than 1% of its total water uptake for metabolic use, Crop water requirement (CWR) can be easily represented by ETc. However our CWR value is in line with the theoretical ETc which clearly indicates level of accuracy. Therefore, it is highly recommendable for the local Commercial Strawberry growers to get robust yield. Asian J. Med. Biol. Res. December 2016, 2(4): 672-677